2013
DOI: 10.1111/j.1540-8183.2013.12020.x
|View full text |Cite
|
Sign up to set email alerts
|

Would Tirofiban Have Been Shown Non‐Inferior to Abciximab Had the TENACITY Trial Not Been Terminated for Financial Reasons?

Abstract: Objectives To investigate whether tirofiban would have been non-inferior to abciximab had the trial completed enrollment, and we place the termination of this trial in a broader research ethics context. Background TENACITY was terminated by the sponsor for financial reasons. At the time, event rates for the 2 treatment arms were unknown. Methods TENACITY was designed to compare tirofiban with abciximab in approximately 8000 patients; however, enrollment was terminated after 383 (4.8%) patients. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…also found a small nonstatistically significant increase in minor bleeding and major bleeding requiring transfusion in the high‐dose tirofiban group. Although ceased prematurely, another recent trial would have likely demonstrated noninferiority of tirofiban over abciximab in terms of MACEs had it been completed . More recently, abciximab and high‐dose, double‐bolus eptifibatide have been shown to have a comparable effect on outcomes in a large number of patients (n=1710) undergoing primary PCI for STEMI, with similar rates of MACEs and major bleeding at 30 days and 3 years .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also found a small nonstatistically significant increase in minor bleeding and major bleeding requiring transfusion in the high‐dose tirofiban group. Although ceased prematurely, another recent trial would have likely demonstrated noninferiority of tirofiban over abciximab in terms of MACEs had it been completed . More recently, abciximab and high‐dose, double‐bolus eptifibatide have been shown to have a comparable effect on outcomes in a large number of patients (n=1710) undergoing primary PCI for STEMI, with similar rates of MACEs and major bleeding at 30 days and 3 years .…”
Section: Discussionmentioning
confidence: 99%
“…Although ceased prematurely, another recent trial would have likely demonstrated noninferiority of tirofiban over abciximab in terms of MACEs had it been completed. 24,25 More recently, abciximab and high-dose, double-bolus eptifibatide have been shown to have a comparable effect on outcomes in a large number of patients (n=1710) undergoing primary PCI for STEMI, with similar rates of MACEs and major bleeding at 30 days and 3 years. 26 Although not powered to compare these events, we have consistent results with these larger studies.…”
Section: Steinhubl Et Al 14 Noted a Nonsignificantly Higher Incidencmentioning
confidence: 99%
“…The MULTISTRATEGY study is one of the larger reports showing non‐inferiority of tirofiban compared to abciximab in primary PCI . This was also suggested in a recent statistical extrapolation of the TENACITY trial . Despite this apparent equivalence, 2 meta‐analyses of abciximab and tirofiban trials were conflicting in their conclusions as to the efficacy of these agents .…”
mentioning
confidence: 99%
“…4 This was also suggested in a recent statistical extrapolation of the TENACITY trial. 5 Despite this apparent equivalence, 2 meta-analyses of abciximab and tirofiban trials were conflicting in their conclusions as to the efficacy of these agents. 6,7 In the high-dose P2Y 12 inhibitors pretreatment era, trials of GPI similarly resulted in differing outcome benefits, ON-TIME 2 8 favoring pretreatment with tirofiban with no benefit from upstream abciximab in BRAVE-3.…”
mentioning
confidence: 99%